Extrathymic induction of Foxp3+ regulatory T cells declines with age in a T‐cell intrinsic manner. Issue 10 (31st July 2013) - Carpentier, Maxime; Chappert, Pascal; Kuhn, Chantal; Lalfer, Mélanie; Flament, Héloïse; Burlen‐Defranoux, Odile; Lantz, Olivier; Bandeira, Antonio; Malissen, Bernard; Davoust, Jean; Gross, David‐Alexandre
<x xml:space="preserve">Abstract</x> Extrathymically induced Foxp3+ regulatory T (Treg) cells contribute to the pool of Treg cells and are implicated in the maintenance of immune tolerance at environmental interfaces. The impact of T‐cell senescence on their generation and function is, however, poorly characterized. We report here that steady‐state induction of Foxp3 is impaired in aged T cells in vivo. In vitro assays further revealed that this defective generation of Treg cells was independent from the strength of TCR stimulation and arose before T‐cell proliferation. Importantly, they also revealed that this impairment of Foxp3 induction is unrelated to known age‐related T‐cell defects, such as IL‐2 secretion impairment, accumulation of activated T‐cell populations, or narrowing of the T‐cell repertoire. Finally, a loss of extrathymic induction of Foxp3 and tolerance to minor‐mismatched skin graft were observed in aged mice treated by nondepleting anti‐CD4 antibody. The T‐cell intrinsic impairment of Treg‐cell generation revealed here highlights age as a key factor to be considered in immune tolerance induction.